Oceanographical engineering - Wiegel, Robert L. (Dover Publications, 2005)
This graduate-level text explores the theory of periodic waves; tsunamis, storm surges, and harbor oscillations; the effect of structures on waves; waves in shoaling water; tides and sea level changes; currents; shores and shore processes; some characteristics of the oceans' waters; moorings; and other related subjects.1964 edition.
Originally published: Englewood Cliffs, N.J. : Prentice-Hall, c1964.
Keywords: Oceanography.; Ocean waves.; Hydraulic structures.; Hydrodynamics.; elektronické knihy; electronic books